Mineral Concentrations in Grazed Cool-Season Annual Grass Pastures in North Florida: AN224/AN224, 8/2009 - Myer, Bob; Chelliah, G.; McDowell, Lee; Wilkinson, Nancy; Blount, Ann; Mackowiak, Cheryl (EDIS, 2009)
AN224, a 3-page illustrated fact sheet by Bob Myer, G. Chelliah, Lee McDowell, Nancy Wilkinson, Ann Blount, and Cheryl Mackowiak, describes information gained from a mineral study component of a four-year grazing study at NFREC Beef Unit, to measure monthly concentrations of selected minerals in forage during the late fall-winter-spring grazing season in north Florida. Published by the UF Department of Animal Science, August 2009.